Evaluation of thermal energy and activated carbon production from bagasse pith - Fatemeh Jadidyan; Mohammad Talaeipoor; Saeed Mahdavi; Amirhoman Hamasi (تحقیقات علوم چوب و کاغذ ایران, 2016)
The purpose of this study is the evaluation of bagasse pith for heating energy and activated carbon production. To assess the energy production of the pith, bulk density, melting point, and heating value were measured. Furthermore, percentage of moisture, ash, volatile compounds, fixed carbon, lignin, and elements contents were determined. Ash and volatile content average were measured at 30.23% and 67.14%, respectively. The bulk density average of the pith powder with 80 meshes was determined at 0.15 g/cm3. Lignin content and melting point of pith is measured 23.1%, and 1050 °C, respectively. Sulfur content is important in terms of environmental pollution and it was determined 0.3%. Gross heating value was measured directly by calorimeter bomb to 10.30 MJ/kg that is lower than bagasse and wood. The activated carbon produced from pyrolysis of bagasse pith was chemically activated with zinc chloride. The chemically activated carbons were characterized by measuring iodine of 504 mg/g, specific surface (BET) of 478 m2/g, and pore diameter of 7.45 nanometer. It is suitable for liquid absorption according to the pore size.